2015
DOI: 10.4103/2279-042x.155758
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam premedication for Ketamine-induced emergence phenomenon: A prospective observational study

Abstract: Objective:Ketamine administration is known to induce hemodynamic pressor response and psychomimetic effects which could be attenuated by appropriate premedication. The present study was designed to evaluate the effect of midazolam on hemodynamic stability and postoperative emergence phenomenon following ketamine anesthesia.Methods:This was a prospective observational study including 30 adult patients with American Society of Anesthesiologists physical grades I and II scheduled for elective short surgeries unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In addition, ketamine-associated delirium occurring at anesthetic doses (1-2 mg/kg, i.v. infusion) is effectively minimized via pretreatment with benzodiazepines (positive allosteric modulators of GABA A receptors; Dundee and Lilburn, 1978;Perumal et al, 2015). In contrast, Irifune et al (2000) showed that both muscimol and the benzodiazepine receptor agonist diazepam augment ketamine-induced anesthesia, whereas the GABA A receptor antagonist bicuculline antagonizes ketamineinduced anesthesia in mice.…”
Section: Gaba Uptake and Gaba Receptorsmentioning
confidence: 99%
“…In addition, ketamine-associated delirium occurring at anesthetic doses (1-2 mg/kg, i.v. infusion) is effectively minimized via pretreatment with benzodiazepines (positive allosteric modulators of GABA A receptors; Dundee and Lilburn, 1978;Perumal et al, 2015). In contrast, Irifune et al (2000) showed that both muscimol and the benzodiazepine receptor agonist diazepam augment ketamine-induced anesthesia, whereas the GABA A receptor antagonist bicuculline antagonizes ketamineinduced anesthesia in mice.…”
Section: Gaba Uptake and Gaba Receptorsmentioning
confidence: 99%
“…IM administration has made it an especially popular choice for sedation in children who may otherwise be uncooperative. Although not as frequently used in adults for this purpose due to an increased likelihood of emergence delirium (1–2% in children vs. 10–20% in adults; Strayer and Nelson, 2008), this can effectively be reduced with benzodiazepine administration (Dundee and Lilburn, 1978; Perumal et al, 2015) or with the co-administration of propofol (Willman and Andolfatto, 2007; Andolfatto and Willman, 2010). …”
Section: Clinical Uses In Medicinementioning
confidence: 99%
“…Following the administration of ketamine, it is important to obtain IV or IO access, monitor oxygen saturations, and ensure an uncompromised airway with consideration for any underlying respiratory comorbidities. Although unlikely during transport, if an emergence reaction occurs following the metabolism of ketamine, administration of midazolam by any route is warranted . Emergency medical service responders have extensive experience with IM midazolam because it is the preferred IM agent in the management of status epilepticus and has a rapid onset of action and short duration of action when compared with other benzodiazepines .…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Although unlikely during transport, if an emergence reaction occurs following the metabolism of ketamine, administration of midazolam by any route is warranted. 34 Emergency medical service responders have extensive experience with IM midazolam because it is the preferred IM agent in the management of status epilepticus and has a rapid onset of action and short duration of action when compared with other benzodiazepines. 35 Although some studies utilized midazolam as adjunct sedation, there is potential concern that such a practice may compound the risk of respiratory compromise.…”
Section: Practical Applicationsmentioning
confidence: 99%